2010
DOI: 10.1007/s10643-010-0405-1
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Difference: Comparing Integrated and Traditional Single-Subject Lessons

Abstract: Early childhood curricula should be authentic and child-centered, however, many teachers still rely on direct instruction lessons. To better define how an integrated curriculum meets the needs of students, this study examined teacher talk and actions during instructional activities with first and second graders under two conditions: (1) subject-integrated social studies lessons of an integrated curriculum unit (experimental condition); and (2) single subject-focused mathematics lessons of a traditional separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Teachers unfamiliar with implementing integrated curricula are advised to ‘start small’ perhaps using a theme (Zhbanova et al, 2010), and to rely less on instruction kits; two things that Ms. Li did. After observing Lesson 8, the principal commented positively and constructively that Ms. Li's teaching was more integrated and consistent with the theme.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers unfamiliar with implementing integrated curricula are advised to ‘start small’ perhaps using a theme (Zhbanova et al, 2010), and to rely less on instruction kits; two things that Ms. Li did. After observing Lesson 8, the principal commented positively and constructively that Ms. Li's teaching was more integrated and consistent with the theme.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…I used resources and props more frequently than in Phase 1 and found myself becoming a little more confident in integrating other subject areas with music. (Interview, 9 June 2009) Teachers unfamiliar with implementing integrated curricula are advised to 'start small' perhaps using a theme (Zhbanova et al, 2010), and to rely less on instruction kits; two things that Ms. Li did. After observing Lesson 8, the principal commented positively and constructively that Ms. Li's teaching was more integrated and consistent with the theme.…”
Section: U S I C C O N C E P T S a N D M O V E M E N Tmentioning
confidence: 99%
“…Zhbanova, Rule, Montgomery, & Nielsen, 2010), the potential educational benefits of IC cannot be realized without teachers' successful implementation of it in their classrooms. The study results expanded our understanding on how IC is being used in early childhood education settings.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1984, the National Association for Core Curriculum examined over eighty studies on the effectiveness of integrative programs and concluded that, in almost every case, the students in integrative programs performed well or better on standardized achievement tests than those students from traditional curriculum programs. Many quantitative and qualitative studies have confirmed the effectiveness of IC and overwhelmingly supported that students can benefit from IC in different areas, such as academic achievement, teamwork, ownership, motivation and attitudes (Cviko, McKenney, & Voogt, 2013;MacMath, Roberts, Wallace, & Chi, 2009;Lewis & Shaha, 2003;Zhbanova, Rule, Montgomery, & Nielsen, 2010). A closer look at the existing literature indicates that a variety of factors may affect IC implementation in schools, including teachers' beliefs in IC, teachers' knowledge and skills in carrying out IC, and many other issues beyond teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students that have interdisciplinary experiences retain their majors and are better prepared for life and careers (Kezar & Elrod, 2012). In the study conducted by Zhbanova et al (2010) comparing integrated with single-subject lessons, they found that students do better with interdisciplinary than conventional single-department programs.…”
Section: Interdisciplinary Expansionmentioning
confidence: 99%